Pediatric hospitalizations for upper urinary tract calculi: Epidemiological and treatment trends in the United States, 2001–2014. Issue 1 (February 2018) - Modi, Parth K.; Kwon, Young Suk; Davis, Rachel B.; Elsamra, Sammy E.; Dombrovskiy, Viktor; Olweny, Ephrem O.
Summary: Introduction: The incidence of urolithiasis in the pediatric population in the United States has steadily been increasing over the past few decades. Few studies to date have examined trends in the hospitalization and inpatient surgical treatment of urolithiasis in the pediatric population using nationally representative data. Objective: The aim was to evaluate nationwide trends in the rates of pediatric hospitalization and inpatient surgical activity for upper urinary tract calculi (UUTC) in the United States from 2001 to 2014. Patients and methods: The National Inpatient Sample (NIS) databases for 2001–2014 were queried. Hospitalizations for patients younger than age 18 (excluding newborns), with principal discharge diagnoses of kidney or ureteral calculi were selected. Surgical procedures during hospitalization were identified. Hospitalization and surgical activity data were analyzed using trends tests, chi-square statistics, and multivariable logistic regression as appropriate. Results: Of an estimated 30.2 million pediatric hospitalizations during the study period, 44, 369 overall (147 per 100, 000) were for UUTC. The total number and proportion of UUTC hospitalizations per 100, 000 all-cause admissions significantly decreased between 2001 and 2014 ( p  < 0.0001) (figure). Surgical intervention was undertaken in 19, 946 (45%) of UUTC hospitalizations, with significantly increasing frequency over the study interval ( p  < 0.0001). Urinary tract drainage was the most frequently performed surgical intervention. On multivariable analysis, significant predictors of a higher likelihood of undergoing inpatient surgical intervention during hospitalization for UUTC included older age, female gender, deficiency anemias, hypertension, neurologic disorders, paralysis, and hospitalization after 2001. Discussion: The declining trend in hospitalization for UUTC likely reflects a shift toward outpatient care for routine cases, reserving hospitalization for sicker patients or those with complications of urolithiasis. Similar to previous studies, we also observed that girls were significantly more likely than boys to be hospitalized for stone disease, and that majority of the stone activity in the pediatric population was in children aged 15–17 years. We also observed a sharp increase in the proportion of hospitalized patients who underwent surgical intervention between 2001 and 2014, but the primary driver of this trend remains uncertain. Conclusion: Pediatric hospitalizations for UUTC in US children significantly decreased between 2001 and 2014, while of those hospitalized the proportion who underwent stone-related surgical intervention significantly increased over the same period. A shift towards outpatient care, reserving hospitalization and inpatient surgical care for sicker patients, those with urolithiasis-related complications, or those who fail conservative management, is a possible explanation for these observed trends. Figure